Case report: Novel mutations in the SPG11 gene in a case of autosomal recessive hereditary spastic paraplegia with a thin corpus callosum - Duan, Ji-Qing; Liu, Hui; Wu, Jia-Qiao (Frontiers in Integrative Neuroscience, 2023)
A 24-year-old man presented with insidious onset progressive gait disturbance and was finally diagnosed with autosomal recessive hereditary spastic paraplegia. Two novel mutations, including a frameshift mutation (c.5687_5691del) and a non-sense mutation (c.751C>T), were identified in the SPG11 gene of the patient through whole genome sequencing. The frameshift mutation of c.5687_5691del leads to a change in amino acid synthesis beginning with amino acid No. 1896 arginine and terminating at the 8th amino acid after the change (p. Arg1896MetfsTer8). The non-sense mutation (c.751C>T) causes the conversion of codon 251st encoding the amino acid Gln into a stop codon (p. Gln251Ter), resulting in premature termination of peptide synthesis. Although confirmation of compound-heterozygosity could not be performed, our findings enriched the phenotypic spectrum of SPG11 mutations related to hereditary spastic paraplegia.